Genetic Evidence that Catabolites of the Entner-Doudoroff Pathway Signal C Source Repression of the σ(54) Pu Promoter of Pseudomonas putida - Velázquez, Francisco (American Society for Microbiology, 2004)
Glucose and other C sources exert an atypical form of catabolic repression on the σ(54)-dependent promoter Pu, which drives transcription of an operon for m-xylene degradation encoded by the TOL plasmid pWW0 in Pseudomonas putida. We have used a genetic approach to identify the catabolite(s) shared by all known repressive C sources that appears to act as the intracellular signal that triggers downregulation of Pu. To this end, we reconstructed from genomic data the pathways for metabolism of repressor (glucose, gluconate) and nonrepressor (fructose) C sources. Since P. putida lacks fructose-6-phosphate kinase, glucose and gluconate appear to be metabolized exclusively by the Entner-Doudoroff (ED) pathway, while fructose can be channeled through the Embden-Meyerhof (EM) route. An insertion in the gene fda (encoding fructose-1,6-bisphosphatase) that forces fructose metabolism to be routed exclusively to the ED pathway makes this sugar inhibitory for Pu. On the contrary, a crc mutation known to stimulate expression of the ED enzymes causes the promoter to be less sensitive to glucose. Interrupting the ED pathway by knocking out eda (encoding 2-dehydro-3-deoxyphosphogluconate aldolase) exacerbates the inhibitory effect of glucose in Pu. These observations pinpoint the key catabolites of the ED route, 6-phosphogluconate and/or 2-dehydro-3-deoxyphosphogluconate, as the intermediates that signal Pu repression. This notion is strengthened by the observation that 2-ketogluconate, which enters the ED pathway by conversion into these compounds, is a strong repressor of the Pu promoter.